Case Report: Is Pneumoperitoneum the Only Indication for Surgery in Necrotizing Enterocolitis? - Wei, Ying; Zhu, Yanhong; Luo, Xiaoping; Chen, Ling; Hu, Xiaolin (Frontiers in Pediatrics, 2021)
Objective: This study aims to explore whether pneumoperitoneum is the only surgical indication for neonates with necrotizing enterocolitis (NEC) and to analyze when early surgical intervention should be considered. Methods: A retrospective case series study was conducted including six neonates with stage 2a−2b NEC who received surgeries without absolute indication but with failed conservative treatment. In the meantime, seven infants who received surgery due to pneumoperitoneum and 32 infants treated with conservative treatment were also included for comparison. Results: Our results indicated that the six infants who received surgical treatment without pneumoperitoneum had a better prognosis compared to the seven infants who underwent surgical treatment after the onset of pneumoperitoneum. None of the infants who received early surgical treatment developed short bowel syndrome or neurodevelopmental impairment, while four out of six infants exhibited growth retardation. On the other hand, a total of five out of the seven infants who received surgical treatment after pneumoperitoneum forfeited further treatment, two developed short bowel syndrome, and one experienced neurodevelopmental impairment. Lower gestational age and birth weight, fetal growth restriction (FGR), perinatal asphyxia, postnatal steroid and vascular active drug use, blood transfusion, and hemodynamic significant patent ductus arteriosus were identified as risk factors associated with surgical repair for infants with NEC. In a laboratory test, infants who needed surgeries had a lower platelet count and a higher C-reactive protein value. Conclusion: Aggressive surgical treatment should be considered in infants with severe necrotizing enterocolitis before the onset of pneumoperitoneum. Lower gestational age and birth weight, FGR, perinatal asphyxia, postnatal steroid and vascular active drug use, blood transfusion, and hsPDA may be associated with surgical repair for infants with NEC.